HUBUNGAN KETERGANTUNGAN PENGGUNAAN SMARTPHONE DENGAN KUALITAS TIDUR REMAJA SMPN 8 SAMARINDA - windi mulyana, dela; Ardyanti, Dian; Tonapa, Emelia (Berajah Journal, 2024)
Smartphones have become an essential need for everyone, especially teenagers. Excessive smartphone use can lead to dependency, which negatively impacts sleep quality due to blue light exposure that disrupts circadian rhythms. This study aims to examine the relationship between smartphone dependency and sleep quality among adolescents at SMPN 8 Samarinda. This quantitative research uses a cross-sectional design with a sample of 74 students who completed the SAS-SV questionnaire to assess smartphone dependency and the PSQI questionnaire to evaluate sleep quality. Data analysis using the Spearman rank test indicated a significant relationship between smartphone dependency and sleep quality, with an r value of 0.389.